Current state of practice in the procurement of information technology solutions: content analysis of software requests for proposals. (14th March 2022) - Nguyen, Phuong H.D.; Lines, Brian C.; Maali, Omar; Sullivan, Kenneth T.; Hurtado, Kristen; Savicky, John
The request for proposal (RFP) process is essential to the subsequent success of software project implementations. The RFP seeks to identify an appropriate software solution to best meet the client organisation's scope and contractually establishes the project's baseline cost and schedule expectations. However, there is a lack of RFP-research related to the current state of practice in software projects. The objective of this study was to address this gap via a content analysis of 250 recent software RFPs across commonly implemented software categories. Results identified the most frequently used evaluation criteria and corresponding weights, procurement schedule durations, anticipated length of contract terms, quantity of itemised requirements documented in the owner's scope, and other pertinent information. Inferential testing found several differences among the different software categories. The findings may be helpful to owner project managers who are tasked with leading their project teams through the early stages of scope development and vendor selection.